REALITAS KONSEP PENDIDIKAN HUMANISME DALAM KONTEKS PENDIDIKAN ISLAM - Saifullah Idris; Tabrani ZA (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2017)
This paper aims to map the reality of the concept of humanism education in the context of Islamic education. Education is one of the most essential keys in human life. In general, education aims to help humans to get the existence of humanity as a whole. Education also aims to make people better in life. Currently education has not been able to achieve the goals and objectives of education itself are humanizing human beings by optimizing all the potential that exists in human beings. On the contrary the education that occurs today only creates a human being a robot or machine that can be controlled. Education as a process of human humanization (humanization) comes from the idea of humanism. This is in line with the basic meaning of humanism as human education. The system of education in Islam built on the basis of humanistic values since its inception appears in accord with its essence as a humanity religion. Islam makes human dimension as the orientation of education. The insight of humanism in education carries the principle of empowering each human being as a free individual to develop its potential. That means education is held to manage and develop the human self in order to become a whole human according to human nature.